2018
DOI: 10.13005/bpj/1450
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Concentrations of Ozone (O3) on Metabolic and Physiological Attributes in Wheat (Triticum aestivum L.) Pants

Abstract: Growth, yield, protein content, net photosynthetic rates, stomatal conductance and amino acid profiles were determined in wheat (Triticum aestivum L) plants in response to 50 ppb O3 during the growing season. This concentration is similar to the concentrations of O3 in ambient air. O3 decreased photosynthetic rates (24%) and stomatal conductance (25%), which were reflected in lower growth and yield in terms of number of grains and 100 grain weight. Scanning electron microscopy showed a collapse in the epiderma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This finding was consistent with the decreased protein levels due to ozone exposure in groundnuts (Sahab et al, 2013) and chickpea seeds (Nickhil et al, 2012). Ozone can reduce protein and amino acid levels (Baqasi et al, 2018). Ozone reactions with proteins can change the nature of polypeptide protein backbones, break peptide bonds, crosslink proteins, and modify amino acid side chains, which result in denatura-tion and to changes in protein solubility (Uzun et al, 2012), resulting in severe protein degradation in aged seeds.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was consistent with the decreased protein levels due to ozone exposure in groundnuts (Sahab et al, 2013) and chickpea seeds (Nickhil et al, 2012). Ozone can reduce protein and amino acid levels (Baqasi et al, 2018). Ozone reactions with proteins can change the nature of polypeptide protein backbones, break peptide bonds, crosslink proteins, and modify amino acid side chains, which result in denatura-tion and to changes in protein solubility (Uzun et al, 2012), resulting in severe protein degradation in aged seeds.…”
Section: Resultsmentioning
confidence: 99%
“…HD 2967 under ambient and elevated (ambient+20 ppb) O 3 stress for 4 hours day −1 from 2 weeks after germination to maturity. Baqasi et al (2018) reported a 49% decline in grain dry mass in wheat after 50 ppb O 3 exposure. Ozone also influences the quality of crops in terms of starch, protein, nutrients, and oil content.…”
Section: Crop Yield and Qualitymentioning
confidence: 99%
“…However, per metre square of crop the starch and grain protein yield is reduced (Broberg et al, 2015;Feng, Kobayashi and Ainsworth, 2008;Gelang et al, 2000). Some wheat cultivars have shown a decrease in grain protein concentration under O3 exposure (Yadav et al, 2019a;Baqasi et al, 2018;Mishra, Rai and Agrawal, 2013). This could be because leaf proteins are being converted to enzymatic antioxidants to provide defence against O3 induced damages, resulting in less proteins available for translocation to the grains (Yadav et al, 2019b;Sarkar et al, 2010;Fatima et al, 2018).…”
Section: #6mentioning
confidence: 99%